2011
DOI: 10.1111/j.1365-2966.2011.18810.x
|View full text |Cite
|
Sign up to set email alerts
|

Galactic fountains and the rotation of disc-galaxy coronae

Abstract: In galaxies like the Milky Way, cold (~ 10^4 K) gas ejected from the disc by stellar activity (the so-called galactic-fountain gas) is expected to interact with the virial-temperature (~ 10^6 K) gas of the corona. The associated transfer of momentum between cold and hot gas has important consequences for the dynamics of both gas phases. We quantify the effects of such an interaction using hydrodynamical simulations of cold clouds travelling through a hot medium at different relative velocities. Our main findin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
176
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(187 citation statements)
references
References 38 publications
10
176
0
1
Order By: Relevance
“…These include a galactic fountain of cool gas that spins up hot gas (Marinacci et al 2011), a hot galactic fountain of superbubble ejecta that produces an exponential disk before cooling, or infall from the cosmic web with some preferential direction. Our measurements cannot, by themselves, distinguish between these models (which may not be mutually exclusive), but they are an important kinematic constraint for future halo and galaxy formation models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a galactic fountain of cool gas that spins up hot gas (Marinacci et al 2011), a hot galactic fountain of superbubble ejecta that produces an exponential disk before cooling, or infall from the cosmic web with some preferential direction. Our measurements cannot, by themselves, distinguish between these models (which may not be mutually exclusive), but they are an important kinematic constraint for future halo and galaxy formation models.…”
Section: Discussionmentioning
confidence: 99%
“…Also, if the material is fresh infall from the cosmic web then it likely accretes along filaments, which lead to a preferential orbital angular momentum axis. Finally, gas ejected from the disk (either cold or hot) could spin up the halo (Marinacci et al 2011), although perhaps not to the velocity that we infer.…”
Section: Halo and Disk Modelsmentioning
confidence: 99%
“…For example, Marinacci et al (2011) and Marasco et al (2012) have suggested gas driven into the hot coronae by recent star formation in the disk may cause the halo gas to cool. This cool gas can then accrete onto the galaxy.…”
Section: The Formation Of Disksmentioning
confidence: 99%
“…Fraternali & Binney 2006) show that there must be additional mechanisms governing the kinematics of extraplanar gas, because these simple models obtain lags that are too shallow compared with observations. A possibility is the interaction between the uplifted gas and a corona of slowly rotating hot gas, which would explain the magnitude of the observed lags (Marinacci et al 2011). Other explanations for the properties of extraplanar gas involve, for example, thermal instabilities in the corona (Kaufmann et al 2006; but see Binney et al 2009), pressure gradients, or the effect of the magnetic field (Benjamin 2002).…”
Section: Introductionmentioning
confidence: 99%